Seasonal abundance of Coricuma nicoyensis Watling and Breedy, 1988 (Crustacea: Cumacea) on a tropical intertidal mud flat. - Vargas, José A. (1989)
A three-year study shows that the cumulous Coricu nicoyensis Watling and Breedy, 1988 shows seasonal abundance in a tropical muddy plain of the intertidal zone in the Gulf of Nicoya (10 N, 85 W), Costa Rica's Pacific coast. Abundance is high during the dry season (December to April) and low in the rainy season (May to November). Seasonal variations of salinity may be the most obvious environmental factor that influences the abundance of this crustacean. However, physiological and reproductive studies are needed to support this inference. C. nicoyensis apparently reproduces throughout the year in the muddy plain, with periods of greater intensity during the dry season.